RANCANG BANGUN PENGONTROL SUHU BAYI NORMAL PADA INFANT WARMER SECARA OTOMATIS - Laili Marwiyah; Salomo Sijabat (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2019)
Infant warmer is a device used to help maintain the warmth of a baby so that the newborn feels the temperature like in the mother's womb. In this infant warmer there are procedures and the main feature is temperature with the main aim to maintain the temperature for the baby to avoid hypothermia. The design of this tool aims to obtain the design of infant warmers using the DHT11 sensor as a temperature indicator displayed on the LCDThis research starts from the stages of gathering various sources, formulating potential problems, gathering information, designing tools, designing and conducting functional tests. This design uses a DHT11 sensor, LCD, heater and driver. After the design has been carried out, testing each series to determine whether the system works in accordance with the theory discussed If you have already done so, then design the infant warmer design using the DHT11 sensor as a temperature indicator with the display on the ATMega8535 microcontroller-based LCD already feasible to use